Baseline characteristics, level of disease severity and outcomes of patients with COVID-19 admitted to intensive care unit in COVID-19 dedicated Mugda Medical College and Hospital, Dhaka, Bangladesh - Hossain, Irin; Khan, Manzurul H.; Tuhin, Shah G.; Aktaruzzaman, M. M.; Rahman, Shafiur; Mullick, Ashekur R.; Shahin, Md.; Yasmin, Nahid; Choudhury, Adnan Y.; Haque, Monjurul (International Journal Of Community Medicine And Public Health, 2020)
Background: Novel coronavirus disease is associated with highly intensive care unit (ICU) mortality. With the dramatic increase of confirmed cases as well as death toll in Bangladesh, timely and effective management of severely and critically ill patients appears to be particularly important. This includes streamlining workflows for rapid diagnosis and isolation, clinical management, and infection prevention. The main objective of this study was identification of the demographic, clinical characteristics, severity and outcome of patients admitted into ICU. Methods: We aimed to describe the demographic and clinical characteristics, severity of disease, management patterns and outcomes of critically ill patients with coronavirus disease 2019 admitted to ICU in a Bangladeshi setting and for this purpose a retro-prospective study of conveniently selected 63 ICU admitted patients with COVID-19 was conducted from May 1 to June 30, 2020. Data were obtained from patient charts and the hospitals’ records using a structured questionnaire. Results: Most of the ICU patients were older male (30, 65.3%) and most of them were 70 or above years of age group (17, 37.0%). ICU patients more likely suffered from comorbidities like hypertension (938, 60.3%); diabetes (36, 57.1%); chronic kidney disease (21, 33.3%). In most cases treatment in ICU included the administration of antibiotics (100.0%) (Meropenem, 20, 31.7%). Forty-Eight patients died (discharge mortality, 76.2%), and fourteen patients were discharged alive from the ICU with a rate of 22.2%. One patient transferred (Palliative discharge, 1.6%) to other facilities for palliative care purpose. Conclusions: Our findings also highlight the importance of planning for mass critical care along with central oxygen supply system as the need for ICU care and ventilator support to treat patients with COVID-19 grows rapidly in Bangladesh.